Use of Google Site Multiplatform in Science Learning to Improve Motivation and Learning Outcomes of Elementary School Students - Faiz, R. Moh Edi; Julianto; Widodo, Wahono (Papanda Publisher, 2025)
Education is the main foundation in shaping a more promising future. This study aims to evaluate how effective the use of multiplatform-based Google Sites in the Natural Sciences (IPA) learning process is as a tool to improve student motivation and learning outcomes at the elementary school level. The study applied the Systematic Literature Review (SLR) approach, which included the stages of identification, selection, and in-depth analysis of relevant scientific publications. Data were collected from various national and international databases such as ERIC, Scopus, and Google Scholar, with selection criteria in the form of publications from the last five years (2023–2025) that discuss the integration of digital technology, learning motivation, and academic achievement in the context of basic education. The results of the analysis show that Google Sites offer high flexibility thanks to their ability to operate on multiple devices, as well as support interactive learning through the use of multimedia elements such as text, images, videos, and quizzes. Other findings show that the use of Google Sites can encourage students' intrinsic motivation by providing an exploratory and student-centered learning space, while strengthening academic achievement through the presentation of structured, engaging, and easily accessible materials. A number of studies reported increased active engagement, learning independence, and concept comprehension after implementing Google Sites-supported learning. Therefore, the integration of Google Sites across multiple platforms in teaching science at the elementary school level has great potential in creating a learning experience that is more adaptive, engaging, and in line with the demands of today's digital age.